2010
DOI: 10.1227/01.neu.0000374768.16291.03
|View full text |Cite
|
Sign up to set email alerts
|

Endocrinopathy, Vision, Headache, and Recurrence After Transsphenoidal Surgery for Rathke Cleft Cysts

Abstract: Surgical fenestration and/or resection of Rathke cleft cyst via the transsphenoidal approach are a rational choice for surgical management of these lesions when symptomatic. In most cases, visual symptoms and headache can be expected to improve. New persistent endocrine deficits can be expected in a small percentage of patients, but preexisting endocrinopathies resolve in many patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 26 publications
3
52
0
Order By: Relevance
“…24,27,28,34,50 This is mainly because some patients underwent GTR. In analyzing the complications with respect to the extent of resection, 47% of patients with GTR had complications, whereas only 8% and 9% of those who underwent TS/STR and TC/STR had complications associated with surgery; this difference was significant (p = 0.002).…”
Section: Outcome Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…24,27,28,34,50 This is mainly because some patients underwent GTR. In analyzing the complications with respect to the extent of resection, 47% of patients with GTR had complications, whereas only 8% and 9% of those who underwent TS/STR and TC/STR had complications associated with surgery; this difference was significant (p = 0.002).…”
Section: Outcome Analysismentioning
confidence: 99%
“…1,23,34 Furthermore, some authors even reported worsened vision after a transsphenoidal procedure due to the fat packing. 26,44,50 In recent years, the supraorbital keyhole craniotomy has been increasingly used to remove tumors of the sellar area. 4,10,18,52 Numerous publications have demonstrated the advantages of this keyhole approach over traditional craniotomy, including minimal exposure, shortened surgical duration, lower morbidity, and satisfactory cosmetic outcomes.…”
Section: Assessment Of Different Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that DI can develop after pituitary region surgery in up to 75% of cases 7,8,12,15,17 and after transsphenoidal surgery in 10%-44% of cases, 4,6,12 whereas hyponatremia can occur in up to 35% of cases after surgery of pituitary region lesions. 12,13 The management of hypernatremia and hyponatremia following pituitary or hypothalamic region surgery can often be complex and dependent on several variables.…”
Section: Discussionmentioning
confidence: 99%
“…Although they are reported in as many as 3-22% of all autopsy studies, they are seldom symptomatic during life [5,6]. The most common clinical symptoms associated with RCCs are headache, impaired visual function, and endocrinological insufficiency [7,8]. RCCs can also cause delayed or precocious puberty, amenorrhea/galactorrhea, growth retardation, weight gain, and hypogonadism [9][10][11].…”
Section: Introductionmentioning
confidence: 99%